Larvicidal Effects of Tithonia diversifolia (Hemsley) A. Gray Leaf Water Extract against Culex sp. Larvae - Hasan Ali Abdurrachman; Diah Dhianawaty; Neneng Syarifah (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: There are various vector mosquitoes that cause filariasis such as Culex sp. Controlling the number of vectors with larvacide can reduce the spread of this disease. The extracts of Tithonia diversifolia (Hemsley) A. Gray leaves are known to have larvicidal effects on Aedes aegypti larvae. The purpose of this study is to determine the larvicidal effects of Tithonia diversifolia (Hemsley) A. Gray leaf water extract against Culex larvae.Methods: This was an experimental study conducted during the period of October to November 2012 at the Laboratory of Biochemistry, Faculty of Medicine, Universitas Padjadjaran. First trials were conducted to find the most effective larvicidal concentration of Tithonia diversifolia (Hemsley) A. Gray leaf water extract in killing 25 Culex larvae. A concentration of 100 ml was decided as the testing concentration which would be compared to a positive control containing Abate® and a negative control containing distilled water. The number of dead larvae was calculated every hour for 48 hours.Results: Effective larvicidal concentration of Tithonia diversifolia (Hemsley) A. Gray leaf water extract was 60% (p=0.000 compared to negative control), which was lower than Abate®. Result also showed LC50 and LC90 of 24% and 42%, respectively.Conclusions: Tithonia diversifolia (Hemsley) A. Gray leaf water extract has a larvicidal effect on Culex sp. larvae, although it is not as effective as Abate®, Hence, this leaf may be used as an alternative larvacide as these plants are easily available in the community and inexpensive.Keywords: Culex sp., filariasis, larvacide, Tithonia diversifolia (Hemsley) A. GrayDOI: 10.15850/amj.v2n1.441